2004
DOI: 10.1104/pp.104.041426
|View full text |Cite
|
Sign up to set email alerts
|

The Spatially Variable Inhibition by Water Deficit of Maize Root Growth Correlates with Altered Profiles of Proton Flux and Cell Wall pH

Abstract: Growth of elongating primary roots of maize (Zea mays) seedlings was approximately 50% inhibited after 48 h in aerated nutrient solution under water deficit induced by polyethylene glycol 6000 at 20.5 MPa water potential. Proton flux along the root elongation zone was assayed by high resolution analyses of images of acid diffusion around roots contacted for 5 min with pH indicator gel. Profiles of root segmental elongation correlated qualitatively and quantitatively (r 2 5 0.74) with proton flux along the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
1
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 53 publications
8
50
1
5
Order By: Relevance
“…However, the turgor pressure along the elongation zone was equally reduced in both well-watered and water deficit-stressed conditions, suggesting that cell wall extensibility is the major factor in the regulation of root cell growth (Spollen and Sharp, 1991;Zhu et al, 2007). In water-stressed roots, a reduced pH was detected in the apical region (Wu et al, 1996;Fan and Neumann, 2004;Fan et al, 2006;Zhu et al, 2007). The acidic pH could be responsible for the acid-induced extensibility that maintains the cell growth rate.…”
Section: Reprps Are Involved In the Regulation Of Cell Expansionmentioning
confidence: 95%
“…However, the turgor pressure along the elongation zone was equally reduced in both well-watered and water deficit-stressed conditions, suggesting that cell wall extensibility is the major factor in the regulation of root cell growth (Spollen and Sharp, 1991;Zhu et al, 2007). In water-stressed roots, a reduced pH was detected in the apical region (Wu et al, 1996;Fan and Neumann, 2004;Fan et al, 2006;Zhu et al, 2007). The acidic pH could be responsible for the acid-induced extensibility that maintains the cell growth rate.…”
Section: Reprps Are Involved In the Regulation Of Cell Expansionmentioning
confidence: 95%
“…In addition, Tabuchi and Matsumoto (2001) suggested that the Aldecreased mechanical extensibility of the CW in wheat roots could be attributed to an increase in ferulic and diferulic acids, which crosslink CW structural components and thus strengthen the CW (Brett and Waldron 1996). The water deficit-enhanced production of phenols in the root tips was made responsible for the progressive growth cessation towards the basal region in the elongation-zone of maize (Fan and Neumann 2004) and soybean roots .…”
Section: Cell-wall Extensionmentioning
confidence: 99%
“…Este resultado de acordo com Fan & Neumann (2004) pode estar relacionado ao fato do PEG ser quimicamente inerte, atóxico para as sementes, simulando a seca e não penetrando no tegumento devido ao tamanho de suas moléculas.…”
Section: Resultsunclassified